Crystal cataracts: Human genetic cataract caused by protein crystallization - Pande, Ajay (The National Academy of Sciences, 2001)
Several human genetic cataracts have been linked recently to point mutations in the γD crystallin gene. Here we provide a molecular basis for lens opacity in two genetic cataracts and suggest that the opacity occurs because of the spontaneous crystallization of the mutant proteins. Such crystallization of endogenous proteins leading to pathology is an unusual event. Measurements of the solubility curves of crystals of the Arg-58 to His and Arg-36 to Ser mutants of γD crystallin show that the mutations dramatically lower the solubility of the protein. Furthermore, the crystal nucleation rate of the mutants is enhanced considerably relative to that of the wild-type protein. It should be noted that, although there is a marked difference in phase behavior, there is no significant difference in protein conformation among the three proteins.